Rancang Bangun Sistem Informasi Penjualan Berbasis Web Pada UMKM ZXID Di Kota Batam - Arif Rahman Hakim; Tukino Tukino (LPPM Universitas Putera Batam, 2023)
The development of technology is currently growing, one of them is the online development, which is very fast, many companies have started to offer their spare parts online in order to make the most profit, so the competition between companies is growing